Quantitative analysis of circular dichroism at higher-order resonance of extrinsic plasmonic chiral nanostructures using multipole decomposition combined with the optical theorem - Guodong Zhu; Haonan Wei; Zhiguang Sun; Jiayi Liu; Xinran Wei; Yuzhang Liang; Wei Peng; Yurui Fang (New Journal of Physics, 2023)
Plasmonic chirality, which has garnered significant attention in recent years due to its ability to generate strong near-field enhancement and giant circular dichroism (CD). Currently, various theories have been proposed to explain plasmonic extrinsic chirality, however, a comprehensively quantitative explanation for the high-order optical response of extrinsic metamolecule has yet to be established. Herein, we present a concise and quantitative explanation of the giant high-order extrinsic CD of a plasmonic nanocrescent, which origins from multipole decomposition in combination with the optical theorem. Our findings indicate that the high-order resonance modes exhibit giant CD comparable to dipolar modes and can be conveniently applied to the chiral recognition of metamolecules. Furthermore, the nonradiative electric quadrupole resonance exhibits enormous electric field enhancement near metamolecule, which has great application potential in the fields of molecular recognition and sensing in the visible region.